Porcine Epidemic Diarrhea Virus Infection Subverts Arsenite-Induced Stress Granules Formation - Guo, Xiaozhen; Yu, Kejian; Xin, Zhonghao; Liu, Liping; Gao, Yuehua; Hu, Feng; Ma, Xiuli; Yu, Kexiang; Li, Yufeng; Huang, Bing; Yan, Zhengui; Wu, Jiaqiang (Frontiers in Microbiology, 2022)
Stress granules (SGs) are dynamic cytoplasmic protein-RNA structures that form in response to various stress conditions including viral infection. Porcine epidemic diarrhea virus (PEDV) variant related diarrhea has caused devastating economic losses to the swine industry worldwide. In this study, we found that the percentage of PEDV infected cells containing SGs is nearly 20%, meanwhile PEDV-infected cells were resistant to sodium arsenite (SA) induced SGs formation, as demonstrated by the recruitment of SGs marker proteins, including G3BP1 and TIA1. Moreover, the formation of SGs induced by SA treatment was suppressed by PEDV papain-like protease confirmed by confocal microscopy. Further study showed that PEDV infection disrupted SGs formation by down-regulating G3BP1 expression. Additionally, PEDV replication was significantly enhanced when SGs assembly was impaired by silencing G3BP1. Taken together, our findings attempt to illuminate the specific interaction mechanism between SGs and PEDV, which will help us to elucidate the pathogenesis of PEDV infection in the near future.